Semiotic Analysis on The Podcast "How to Build Muscle" on Huberman Lab Clips YouTube Channel - Hasan, Fadhlan Halim; Hikmat, Mahi A; Sakinah, R. Myra Nur (Linguistics and ELT Journal, 2025)
Nowadays, fitness podcasts are becoming popular, they now influence the public’s perception of science and the body. This study analyzes how Huberman Lab podcast episode “How to Build Muscle” explains scientific knowledge about muscle hypertrophy and is understood in different cultures. The most important part is to uncover the various meanings in the podcast’s words using Roland Barthes’ theory. A research design using qualitative methods. Data from the official podcast video and text were used, which were then studied through a model with three steps: reducing data, presenting it, and coming to conclusions. Barthes’ theory was used to find out the denotative, connotative, and myth meanings in certain chosen excerpts. It is found that scientific explanations in the podcast help transmit facts, yet also back up cultural views on having an ‘ideal body’, male/female differences, and the power of science. It is clear from the results that modern fitness discussion combines facts about biology with different ideologies. By exploring this area, the study helps readers gain a new way to view the role of scientific communication in popular media on people’s views of identity, health, and the body.